Molecular and Cellular Effects of Nutrition on Disease Processes 1998
DOI: 10.1007/978-1-4615-5763-0_5
|View full text |Cite
|
Sign up to set email alerts
|

The molecular basis for the role of zinc in developmental biology

Abstract: Zine regulates the gene expression maehinery. It affects the structure of chromatin, the template function of its DNA, the activity of numerous transcription factors and ofRNA polymerases. Hence, it determines both the types of mRNA transcripts synthesized and the rate of transcription itself. Alterations in one or more of these zinc dependent processes have been proposed to account for the proliferative arrest and teratology induced by zinc deficiency. To examine this proposal, studies ofzine duringX laevis d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
1
5

Year Published

2000
2000
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 56 publications
0
54
1
5
Order By: Relevance
“…High levels of selenium are found in brazil nuts, kidney, seafood and cereals, although this is soil dependent and it has been reported that European intake of selenium is falling [31]. Zinc acts as a co-factor for enzymes promoting DNA transcription and protein synthesis [32], has a role in expression of steroid hormone receptors [33] and has anti-apoptotic [34] and anti-oxidant properties [35]. Studies have demonstrated that a zinc deficiency can lead to subfertility and abnormal reproductive outcomes [36], and to pregnancy complications [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…High levels of selenium are found in brazil nuts, kidney, seafood and cereals, although this is soil dependent and it has been reported that European intake of selenium is falling [31]. Zinc acts as a co-factor for enzymes promoting DNA transcription and protein synthesis [32], has a role in expression of steroid hormone receptors [33] and has anti-apoptotic [34] and anti-oxidant properties [35]. Studies have demonstrated that a zinc deficiency can lead to subfertility and abnormal reproductive outcomes [36], and to pregnancy complications [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…The potential importance of zinc to the gene can be appreciated from the fact that a great percentage of the zinc content of rat liver is found in the nucleus and a sigin vitro (Cousins, 1998). Zinc is also involved in the processes of genetic stability and gene expression in a variety of ways including the structure of chromatin, the replication of DNA and transcription of RNA through the activity of transcription factors and RNA and DNA polymerases, as well as playing a role of DNA repair and programmed cell death (Falchuk, 1998). Further, zinc is known to regulate both enzyme activity and the stability of the proteins as an activator or as an inhibitor ion (Brandt et al, 2009;Kawashima et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…24) Being an essential trace element, the zinc ion is required as a co-factor for many biological activities involved in cellular metabolism and gene regulation. 27) Plant Ec genes are conspicuously expressed during embryogenesis, analogous to mammalian MT genes. The hepatic concentration of MTs, primarily zinc MT, is 20-fold greater in neonatal than in adult rats.…”
Section: Discussionmentioning
confidence: 99%